Political Reconstruction of Justice of Juvenile Criminal Law in the Diversion Mechanism in the Investigation Process - Parman Gultom; Fauzie Yusuf Hasibuan; Maryano Maryano (International Journal of Law, Crime and Justice, 2025)
This study examines the political reconstruction of fair juvenile criminal law in the diversion mechanism at the investigation stage in Indonesia. The background of the research departs from the gap between the empirical conditions (das sein) and the ideal conditions (das sollen) mandated by the Law on the Juvenile Criminal Justice System UU SPPA and the principle of the best interest of the child in the Convention on the Rights of the Child. The research method used is normative legal research with legislative, case, and comparative approaches. The results of the study show that the implementation of diversion faces obstacles in substance, structure, and legal culture: procedural uncertainty, limited capacity of apparatus, lack of supporting facilities, and weak coordination across institutions. This research offers a reconstruction of legal politics in these three domains at once substance, structure, and culture so that diversion truly becomes an instrument of restorative justice that restores, not punishes. The scientific contribution of this article lies in the formulation of a multi-layered policy model, the elaboration of performance indicators for the implementation of diversion at the investigation stage, as well as a matrix of operational recommendations for stakeholders at the police, prosecutor's office, court, and child social service institutions.